Developing Speaking Skills in Lower-Secondary Learners: Focus on Feedback - Tomášková, Magdalena (Univerzita Pardubice, 2020)
This bachelor thesis deals with development of speaking skills in lower-secondary learners with a focus on feedback. The theoretical part introduces communicative competence which is more specified for developing speaking skills in lower-secondary learners. Furthermore, it discusses varieties of speaking tasks through which the speaking skills can be developed. Finally, it defines feedback and discusses different techniques of teacher´s provision of feedback and their efficiency during speaking activities. The practical part examines which feedback techniques are used in practice and if they are in alignment with the aim of the activity.
Rozvoj dovednosti mluvení u žáků na 2. stupni základní školy se zaměřením na zpětnou vazbu
Keywords: communicative competence; speaking tasks; feedback; alignment; komunikační kompetence; mluvní aktivity; zpětná vazba; soulad